BIOPROSPECÇÃO DA GEOPRÓPOLIS DE MELIPONA FASCICULATA SMITH COMO INSUMO NA GERAÇÃO DE PRODUTOS LEISHMANICIDAS - DUTRA, Richard Pereira (2012)
Melipona fasciculataSmith, occurs in Brazil, especially in the state of Maranhão, where it is popularly known as tiúba . The tiúba produces honey, wax, pollen and geopropolis. The aim of this study was to evaluate the leishmanicidal activity of different samples of geopropolis Melipona fasciculata, aiming to produce a product with leishmanicidal activity. Geopropolis samples were collected in different localities of the municipality of Fernando Falcão-MA and subjected to extractive process withhydroalcoholic solution, obtaining the hydroalcoholic extracts of geopropolis (HEG1, and HEG2 HEG3). The extracts were used for in vitro evaluation of leishmanicidal action, using promastigotes of Leishmania amazonensis. The HEG1, with the highest leishmanicidal activity, was subjected to liquid-liquid partition, resulting in hexanefraction (FH), chloroform fraction (CF), ethyl acetate fraction (AF) and hydroalcoholic fraction (FHA). The fractions were assessed for leishmanicidal activity and antioxidant, and also analyzed for total polyphenol concentration and chemical composition. Extracts of geopropolis showed inhibitory concentration (IC50) between 47-229 μg/mL. The most active extract was EHG1 and its most active fraction was the FA with IC50 of 29.89 μg/mL, while the IC50 FC fractions and FHA showed IC50of 43.21 μg/mL and 49.48 μg/mL, respectively. The HEG1 and fractions leishmanicidalshowed antioxidant activity towards DPPH and high levels of total polyphenols. The hexane fraction showed no leishmanicidal action, and had the lowest antioxidant concentrations of polyphenols. The extracts showed phenolic acids, organic acids, fatty acids, anthraquinones, sugars and alcohols, the analysis by gas chromatography-mass spectrometry (GC-MS). The most active fraction (AF) showed mainly gallic acid, while the other fractions were identified fatty acids, organic acids, anthraquinones, diterpenes, triterpenes, steroids, sugars and alcohols. In the analysis by High performance liquidchromatographycoupled tomass spectrometry (HPLC-MS) extract the most active fraction were identified phenolic acids, ellagitannins and gallotannins, confirming the data obtained by GC-MS. Based on the results obtained was a byproduct that when tested under the same conditions also showed leishmanicidal action. In conclusion, the leishmanicidal activity of geopropolis Melipona fasciculata is likely to be related to the presence of gallic acid derivaties and ellagic.